1995
DOI: 10.1109/68.372748
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency planar microcavity LED's: comparison of design and experiment

Abstract: This paper describes the design of substrate emitting microcavity LED's and a comparison of experimental results with modeling results. The modeling is based on a simulation tool which accounts for guided modes, quantum well reabsorption and photon recycling. The overall quantum efficiencies of X/2 and X cavities both with a 60% and a !M% reflecting DBR mirror are compared and a good qualitative correspondence is found between theory and experiment. The maximum theoretical overall quantum efficiency for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 13 publications
3
32
0
Order By: Relevance
“…Due to a redirection of the Airy mode inside the escape window, the extraction efficiency of RCLED is higher than that of the conventional LED. Besides, RCLED also takes the advantages of lower divergence of output beams, higher spectral purity, better temperature stability and higher modulation bandwidth as compared to the conventional LEDs [7][8][9][10][11]. Some pioneers have presented the effects of emission color and view angle for OLED with SiO 2 /Si 3 N 4 DBRs.…”
mentioning
confidence: 96%
“…Due to a redirection of the Airy mode inside the escape window, the extraction efficiency of RCLED is higher than that of the conventional LED. Besides, RCLED also takes the advantages of lower divergence of output beams, higher spectral purity, better temperature stability and higher modulation bandwidth as compared to the conventional LEDs [7][8][9][10][11]. Some pioneers have presented the effects of emission color and view angle for OLED with SiO 2 /Si 3 N 4 DBRs.…”
mentioning
confidence: 96%
“…Streubel et al [5] indicated that RCLEDs have an extraction efficiency of one order in magnitude than the conventional planar LEDs, and this result has been proven in many literatures [6][7][8]. Besides, RCLEDs also have the advantages of lower divergence of output beams, higher spectral purity, better temperature stability and higher modulation bandwidth as compared to the conventional LEDs [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 86%
“…Due to a redirection of the Airy mode inside the escape window, the RCLEDs have higher extraction efficiency than the conventional LEDs. Streubel et al [16] indicated that RCLEDs have an extraction efficiency of one order in magnitude stronger than the conventional planar LEDs, and this result has been proven in many literatures [17][18][19]. In order to perform the practicability of LPD-ZnO, the textured LPD-ZnO film was applied to AlGaInP/GaInP resonant cavity light emitting diodes (RCLEDs) to meliorate the extraction efficiency.…”
Section: Introductionmentioning
confidence: 96%